An Avionics Platform for Multi-instrument Survey Navigation. (7th March 2016) - Jones, David H.; Jordan, Tom A.; Robinson, Carl
Abstract : The British Antarctic Survey regularly conducts airborne surveys with Twin Otter aircraft equipped with a variety of instruments. Each instrument captures its specific navigation requirements in a dedicated cockpit display that is unique and incompatible with that of other instruments. This creates unwanted logistical problems and training requirements, and necessitates extra air safety certification. In this paper we describe a new avionics display that is sufficiently flexible to capture the requirements of all of our instruments, as well as all of the preferences of our pilots. This Airborne Survey Navigation Device (ASCEND) dynamically routes aircraft within the constraints of the survey and features flexible and intuitive planning and navigation interfaces. ASCEND has been tested and compared to the instrument specific displays and is preferred, both for its ease of use and also for the effective accuracy of the pilot following a survey line.